Answer:
[tex]RQ = SQ[/tex]
Step-by-step explanation:
Given
△RQP ≅ △SQP
See attachment
Required
Additional information that shows that △RQP ≅ △SQP
△RQP and △SQP share a common side QP:
This implies that:
[tex]QP = QP[/tex] ---- Side (S)
△RQP ≅ △SQP implies that:
[tex]\angle RQP = \angle SQP[/tex] ---- Angle (A)
Lastly, we already established that △RQP and △SQP share a common side QP
Then remove point P, we have: RQ and SQ
This implies that:
[tex]RQ = SQ[/tex] --- Side (S)
Hence, the additional piece of information needed is: [tex]RQ = SQ[/tex]